Guru Abdi's Short Story A Servant's Ideal Self-Representation - Paramitha, Ni Made Ayu Susanthi Pradnya; Artayasa, I Wayan; Yus Aditya, I Wayan; Puspita Sari, Ni Kadek (Jayapangus Press, 2025)
The teaching profession plays a crucial role in shaping the future of younger generations. However, in many regions, the welfare and recognition of teachers do not align with the significance of their contributions to society. This social inequality serves as one of the main inspirations behind I Made Sugianto’s literary work, particularly his short story Guru Abdi, featured in the collection Ngipiang Jokowi. This study aims to explore how the short story reflects the psychological experiences of teachers, especially in relation to self-concept and societal recognition. Using a qualitative descriptive method, data were collected through literary analysis and interviews. The study applies Carl Rogers' theory of self-concept, supported by Higgins' discrepancy theory, to analyze the main character, Kadek Arya. The findings reveal a state of congruence in Kadek Arya’s self-concept despite facing numerous challenges, which fosters a consistent positive attitude. Although moments of fear and anxiety-indicative of agitation-related self-do emerge, they do not diminish his overall optimism and dedication. This research concludes that literary works such as Guru Abdi can serve as reflective mediums that highlight the inner strength and resilience of teachers in the face of societal undervaluation.